2021
DOI: 10.3390/su13073707
|View full text |Cite
|
Sign up to set email alerts
|

Precision Agriculture Digital Technologies for Sustainable Fungal Disease Management of Ornamental Plants

Abstract: Ornamental plant production constitutes an important sector of the horticultural industry worldwide and fungal infections, that dramatically affect the aesthetic quality of plants, can cause serious economic and crop losses. The need to reduce the use of pesticides for controlling fungal outbreaks requires the development of new sustainable strategies for pathogen control. In particular, early and accurate large-scale detection of occurring symptoms is critical to face the ambitious challenge of an effective, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 142 publications
1
10
0
Order By: Relevance
“…Ornamental plants have surrounded humans living environmentally since the Neolithic period and have appeared in early Chinese poems and paintings, Egyptian pyramid morals and European history, indicating that humans have a long history of being attracted to ornamental plants [57,58]. Nowadays, ornamental plants, especially flowering plants, are an important part of urban forests, which are planted across all urban areas for enhancing the visual and aesthetic quality of the architectural environments, tolerating the stress of copper (Cu), deicing reagents and drought stress, improving the air quality and fungal disease management, remediating the pollution of on-site greywater, eutrophication, ozone, VOCs, lead (Pb), tin (Sn) and petroleum hydrocarbons [59][60][61][62][63][64][65][66][67][68][69]. Ornamental plants are a more viable choice with high diversity and abundance [1,6].…”
Section: Introductionmentioning
confidence: 99%
“…Ornamental plants have surrounded humans living environmentally since the Neolithic period and have appeared in early Chinese poems and paintings, Egyptian pyramid morals and European history, indicating that humans have a long history of being attracted to ornamental plants [57,58]. Nowadays, ornamental plants, especially flowering plants, are an important part of urban forests, which are planted across all urban areas for enhancing the visual and aesthetic quality of the architectural environments, tolerating the stress of copper (Cu), deicing reagents and drought stress, improving the air quality and fungal disease management, remediating the pollution of on-site greywater, eutrophication, ozone, VOCs, lead (Pb), tin (Sn) and petroleum hydrocarbons [59][60][61][62][63][64][65][66][67][68][69]. Ornamental plants are a more viable choice with high diversity and abundance [1,6].…”
Section: Introductionmentioning
confidence: 99%
“…Extraction of the most significant spectral information from the big dataset is crucial to simplify the production of optoelectronic sensors, suitable for plant disease detection 41 specifically aiming to cheap and innovative surveying devices, to support sustainable disease management in greenhouse or open-field conditions. On perspective, this technology, possibly integrated with different sensors (i.e., thermal sensors and/or 3-D shape sensors) 67 , can improve pathogen detection, since the availability of significant spectral information linked to machine vision-based remote sensing makes feasible the real-time mapping of disease management.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed nano-particle-based products such as nanocarriers for fungicides and RNA-interference molecules offer a better option as these products are less toxic and have a longer shelf-life, and are therefore less harmful to the environment [ 153 , 154 , 155 ]. Multifaceted studies which include the role of secondary metabolites in pathogenesis, combined with nanotechnology, could be noteworthy for developing more sustainable and specific control methods as alternatives to chemical-based approaches [ 156 , 157 , 158 ].…”
Section: Challenges and Perspectivementioning
confidence: 99%